2007
DOI: 10.1002/ijc.22937
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐VEGF‐A therapy reduces lymphatic vessel density and expression of VEGFR‐3 in an orthotopic breast tumor model

Abstract: Because metastasis contributes significantly to cancer mortality, understanding its mechanisms is crucial to developing effective therapy. Metastasis is facilitated by lymphangiogenesis, the growth of new intratumoral or peritumoral lymphatic vessels from pre-existing vessels. Vascular endothelial growth factor A (VEGF-A) is a well-known angiogenic factor. Increasing evidence implicates VEGF-A in lymphangiogenesis, although the mechanism of its pro-lymphangiogenic effect is poorly understood. We examined the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 61 publications
7
71
0
2
Order By: Relevance
“…[29][30][31][32] It has also been demonstrated that TSP1 can mediate tumor growth suppression via blocking angiogenesis, consistent with our results. 33,34 As previously mentioned HuR has been described to stabilize TSP1 and VEGF mRNA resulting in greater levels and increased protein expression.…”
Section: Discussionsupporting
confidence: 92%
“…[29][30][31][32] It has also been demonstrated that TSP1 can mediate tumor growth suppression via blocking angiogenesis, consistent with our results. 33,34 As previously mentioned HuR has been described to stabilize TSP1 and VEGF mRNA resulting in greater levels and increased protein expression.…”
Section: Discussionsupporting
confidence: 92%
“…Double staining for CD31 and LYVE-1 showed that a small population of cells in the periphery was doubly positive for both (Fig. 4B), consistent with previous findings (26,27). Importantly, E7080 treatment dramatically inhibited the numbers of CD31-and LYVE-1-positive cells (Fig.…”
Section: E7080 Inhibition Of Angiogenesis and Lymphangiogenesis In Mesupporting
confidence: 89%
“…39 Indeed, inhibition of VEGF-A expression is associated with decreases in tumor lymphangiogenesis and metastasis. 40,41 Moreover, a reduction in metastasis by downregulation of VEGF-A may be responsible for inhibition of angiogenesis and lymphangiogenesis in tumors, prevention of angiogenic switching in micrometastases and blockage of macrophage recruitment. 42,43 AntiVEGF-A therapy reduces lymphatic vessels and expression of VEGFR-3 in an orthotopic breast tumor model, 41 which may be the mechanism for the anti-metastasis effect.…”
mentioning
confidence: 99%